A force in education - Rice, Ada (My University, 1895)
Introduction: That education is necessary to the advancement of all peoples is a fact of history. That the lack of education is the cause of a large majority of our paupers and criminals, is also an established fact. When uprisings occur in our great cities and our best institutions of law and order are in danger, we find, upon investigation, that the education of the instigators has been “one sided.” The influences which have surrounded them have failed to educate them in any of the essentials of right living, ideal citizenship manhood, and good citizenship. John Stuart Mill says, “Education includes everything that brings us nearer the perfection of our nature.” While Henry George similarly defines it as that which enables a man to more effectively use his natural powers. It is, then, the harmonious development of all our nature, mental, moral and physical. Developing only the intellect and leaving out heart culture makes as we said before a “one sided” boy or man, and this may, and often does, lead to crime.
Citation: Rice, Ada. A force in education. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Education; Home school; Theses; Manuscripts (documents)